Risk Factors Involved in Recurrence of Pterygium Excision after Surgical Excision - Muhammad Waseem, Shahid Anwar Bhatti, Muhammad Ayub Khan, Zaheer Uddin Babar, Abdul Rafe, Haroon Saleem (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the effect of the type and size of growth, sex and patients age, and the application of mitomycin-C intraoperatively and its application duration effect on pterygium recurrence afterwards excision. Study Design: A retrospective and descriptive case series. Place and Duration: In Alshifa Trust Eye Hospital, Rawalpindi and the department of Ophthalmology CMH, Lahore for the duration from November 2022 to April 2022. Methods: Data files from 80 patients (80 eyes) who underwent bare sclera technique surgery with MMC at 0.2 mg / ml (0.02%) and application time ranging from 1 to 5 mints. The study included 60 males and 20 females with 46.4 years of mean age (16 to 60 years). Cases were classified according to sex, age, pterygium type and size and MMC application time. The main outcome measures were to compare the eye affected by the pterygium for any type of recurrence after at least 1-year of follow-up. Results: In our case series, the rate of pterygium recurrence was 10% in the mean follow-up of 1 year. The influencing factors like younger age at admission (<50 years), secondary pterygium (p = 0.330) was suggestively related with pterygium recurrence. There was a clear tendency of less rate of recurrence with smaller pterygium size, with MMC administration times greater than 3 minutes. However, it was not possible to obtain statistical significance due to the smaller sample size. Conclusions: This study results propose that younger age < 50-years, a history of multiple recurrences, increased size and a duration of MMC administration < 3 mints are risk factors for postoperative recurrence of pterygium.